Dynamics of depressive symptoms and within-country migration among Peruvian women - Akram Hernández-Vásquez; Carlos Rojas-Roque; Rodrigo Vargas-Fernández; Guido Bendezu-Quispe (James Cook University, 2020)
Introduction: Peru has experienced a significant internal migration from rural to urban areas in recent years. This study estimates the prevalence of depressive symptoms in Peruvian women of childbearing age and their probability of having these symptoms according to the condition of internal migration. Methods: Data from the 2014-2018 Demographic and Family Health Survey (ENDES) was used. Depressive symptoms were measured using the Patient Health Questionnaire (PHQ-9). Adjusted odds ratios and the marginal effects were estimated to assess associated factors and the probability of having depressive symptoms in relation to internal migration status, respectively. Results: The prevalence of depressive symptoms (PHQ-9≥10 points) decreased from 2014 to 2018, as did the prevalence of these symptoms for all the internal migration status. There was a positive relationship between the post-migration residence time and the probability of having depressive symptoms. Furthermore, compared to women in rural areas who never migrated, all of the other migrant statuses were associated with an increased probability of depressive symptoms. Other factors such as being the head of the household, being married/cohabiting or separated/divorced/widowed, smoking, alcohol consumption, diabetes, having an impairment and living at levels of altitude greater than 500 m were associated with a higher probability of having depressive symptoms. Conclusion: Despite a reduction in the overall burden of depressive symptoms, the migrant subgroup population has a higher probability of presenting these symptoms. Mental health strategies for migrant women are a priority in Peru.